(untitled) (GEON Journal (Management, Organizations and Business), 2017)
Economic globalization under the precept of competitiveness has generated the need to raise their quality standards to all organizations that take on the challenge of prevailing in their environment. Public education institutions have not been outside this scenario of the world economy, so they must make adjustments to their strategic factors and human management is one of them. The University of the Llanos has undertaken over the past decade, a reform process to strengthen its strategic elements adjusting management processes such as personnel administration, recruitment and selection, and performance evaluation. In this process are successes and recommendations for each to achieve the standards required by the new national and world stage.